STUDI ANALISIS INDEKS KEPUASAAN STAKEHOLDERS TERHADAP PELAYANAN PUBLIK PADA BAGIAN HUMAS UIN SUNAN KALIJAGA YOGYAKARTA (Profetik: Jurnal Komunikasi, 2017)
This study aims to determine the index of stakeholders satisfaction to the public service at the Public Relations of UIN Sunan Kalijaga and to determine the factors that affect stakeholders index satisfaction to public services. This type of research is quantitative research with descriptive approach. The research location were ini UIN Sunan Kalijaga Yogyakarta, especially the public relations department. Data collection techniques used include questionnaires to a number of respondents, documentation and literature studies and interview. The results showed that in terms of the dimensions of Peoples Satisfaction Index (PSI) of service provided is considered good. It shows that in this dimension people are satisfied with the services provided by government officials. The factors that influence is a factor of human resources and infrastructure. Suggestions in this research is in order fulfilling service satisfaction remained servicing stakeholders it should be maximized although constrained by several supporting facilities and infrastructure. Service quality improvement through the human resources (HR) are well established and quality must be maintained and even enhanced by efforts to collaborate with other agencies or institutions that can provide training in the form of excellent service. Leaders have to think to reward employees achievers in order to be motivated in delivering services to its stakeholders.